Legal challenges facing electronic litigation and ways to address them - Qadir, Asst.Prof.Dr.Awat Qadir; Ali, L.Dr.Sirwan Raouf Ali (Sulaimani Journal for Humanities, 2025)
It is well known that technological advancements have had a clear and significant impact on all aspects of life. To keep pace with this progress, adapting has become essential. It is rare to find a public or private institution or facility that has not been affected by these developments. The judiciary is one of the most important institutions in the country, and it has been significantly impacted by these advancements. Traditional litigation and its procedural methods have become almost obsolete in modern procedural law. Most modern legal research focuses on implementing new and modern methods in litigation, enabling the judiciary to benefit from the vast array of electronic programs available to deliver its services. Adopting any new legal system may encounter difficulties or challenges from the tangible legal reality. However, the existence of these difficulties does not mean abandoning the modern idea and accepting reality and its lack of development. From this standpoint, we tried to address the numerous difficulties or challenges facing electronic litigation. We defined the scope of our research with the challenges contained in the Iraqi Civil Procedure Law No. 83 of 1969, as well as the challenges contained in the Iraqi Evidence Law No. 107 of 1979. We followed the method of text analysis, in which we tried to analyze the legal texts that are affected by this new system of litigation, how to adapt them to it, and how to overcome these challenges through legislative intervention where it is needed. We tried to reinforce these positions with judicial applications where available.